Quaternary marine tephrochronology of Rock Garden accretionary ridge, Hikurangi Subduction Margin, New Zealand - Schwarze, Cornelius; Hopkins, Jenni L.; Storm, Sonja; Orpin, Alan; Schmitt, Axel Karl; Kukowski, Nina (Journal of volcanology and geothermal research, 2022)
The Taupō Volcanic Zone (TVZ) of the North Island, New Zealand (NZ), is one of the most active Quaternary rhyolitic systems globally, producing voluminous eruptions and associated tephra that punctuate the NZ stratigraphic record. Due to dominantly westerly winds tephras are well preserved in the marine sedimentary record off NZ's east coast and provide important isochrons for chronostratigraphic correlation of marine sediment cores. Two MeBo200 (Bremen seafloor drill rig) sediment cores (GeoB20824-4 and GeoB20846-1) were collected from Rock Garden (RG) offshore of Hawke Bay in water depths of 610-670 metres below sea level (mbsl) with 24 tephra beds (both primary and secondary) that provide a well-dated proximal marine record of TVZ volcanism. The tephra layers are dated by a combination of accelerator mass spectrometry (AMS) 14C of the underlying biogenic carbonates, secondary ion mass spectrometry (SIMS), and correlation of onshore deposits using geochemical fingerprinting. Here we present SIMS U-Pb dating of 189 zircons extracted from five tephra layers from core GeoB20824-4 and six from core GeoB20846-1. AMS radiocarbon ages were carried out on sediments at three depths in core GeoB20824-4 and two depths in core GeoB20846-1, all within the upper 4 metre below seafloor (mbsf). We present major element data for 11 tephra deposits from core GeoB20824-4 and 13 from core GeoB20846-1 analysed by electron microprobe (748 analyses). We identify 10 significant Quaternary tephra horizons including: Kawakawa/Oruanui, Onepuhi (or Rangitawa), Kaukatea, Kidnappers-B, Potaka/Kidnappers, Rewa, and Sub-Rewa. Three tephra layers are geochemically correlated to unnamed but previously recognized tephra from Ocean Drilling Program (ODP) cores further east of RG. In addition to these previously identified tephra, several tephra layers are present in both MeBo200 cores that have not been recognized in existing published on- or offshore records. We attribute the finding of these new tephra deposits to the proximal location of the cores to the source location (unlike existing ODP records), the expanded stratigraphic record at these proximal locations afforded by the new coring technique applied here, and the potentially poor preservation of equivalent deposits in the terrestrial record. The identification of Quaternary TVZ tephras within MeBo200 cores, and their correlation to on- and offshore records is a significant advance as it provides: (1) a tool for correlation of marine sediment cores at the tectonostratigraphically important RG site, (2) a more detailed history of the TVZ from a proximal marine tephra record, (3) a well-dated tephra bed record from marine sediment cores with radiocarbon ages for younger ( ≤45 kyr), and U-Pb zircon ages for older (up to 1.3 Myr) tephra beds, and (4) a first approximation to the regional tephra distribution of key tephra beds